Pemutihan dan Pengikatan Silang Pati Sagu dan Penggunaannya Untuk Bahan Substitusi Pada Pembuatan Bihun - Chatarina Lilis Suryani; Haryadi Haryadi (agriTECH, 1998)
Bleaching sago starch was conducted by using Ca002 and NaOCI ranging from 0.00-1.00% with continuous mixing. The use of CaOCl2 at 0.75% gave whitest starch, therefore bleaching using this method was adopted to produce starch for further treatment.The bleached starch was subjected to cross-linking using POCE3 ranging from 0.000-0.025%. Degree .of substitution of the modified starch were 0.0000-0.0018. Higher POCl3 addition resulted higher degree of substitution, with consequences of higher temperature of gelatinization, higher stability of the pastes and higher viscosity of the gels. The cross-linked starch could be used to substitute rice in rice noodle making at 20-60%. Higher degree of substitution and higher proportion of modified starch used gave higher breaking strength and stronger texture of the resulted noodle compared to that made from 100% of 1R-36 rice.